Direct start-up of aerobic granular sludge system with dewatered sludge granular particles as inoculant. (15th January 2023) - Sun, Zhuo; Zhang, Jiaming; Wang, Jin; Zhu, Hongxiang; Xiong, Jianhua; Nong, Guoyou; Luo, Mengqi; Wang, Jue
Abstract: Aerobic granular sludge (AGS) is a promising technology for engineering applications in the biological treatment of sewage. New objective is to skip the conventional granulation step to integrate it into a continuous-flow reactor directly. This study proposed a method for integrating spherical pelletizing granular sludge (SPGS) into a new patented aerobic granular sludge bed (AGSB), a continuous up-flow reactor. AGSB system could be startup directly, and after 120 days of operation, the SPGS maintained a relatively intact spherical structure and stability. With an initial high chemical oxygen demand (COD) volume loading of over 2.0 kg/(m 3 ·d), this system achieved the desired effect as the same as a mature AGS system. The final mixed liquid suspended solids, and the ratio of 30 min–5 min sludge volume index (SVI30 /SVI5 ) were 20, 000 mg/L, and 0.84, respectively. Although hydraulic elution and filamentous bacteria (FBs) had a slightly negative impact on initial phase pollutant removal, the final removal rates for COD, total nitrogen (TN), ammonia nitrogen (NH4 + -H), and total phosphorus (TP) were 90%, 70%, 95%, and 85%, respectively. The presence of specific functional microorganisms promoted the secretion of extracellular polymeric substances (EPS), from 90.65 to 209.78 mg/gVSS. The maturation process of SPGS altered the microbial community structures and reduced the species abundance of microbes in sludge. Highlights: SPGS as inoculants directly started up the aerobic granular system. Higher initial COD content and COD volume loading than other AGS systems for municipal wastewater. SPGS maintained an intact spherical and stable structure during the maturation process. Filamentous bacteria acted as frame support and didn't discount nutrient removal.